2018
DOI: 10.3390/cancers10110419
|View full text |Cite
|
Sign up to set email alerts
|

A Recurrent BRCA2 Mutation Explains the Majority of Hereditary Breast and Ovarian Cancer Syndrome Cases in Puerto Rico

Abstract: Breast cancer is the most common cause of cancer diagnosis in women and is responsible for considerable mortality among the women of Puerto Rico. However, there are few studies in Puerto Rico on the genetic factors influencing risk. To determine the contribution of pathogenic mutations in BRCA1 and BRCA2, we sequenced these genes in 302 cases from two separate medical centers, who were not selected for age of onset or family history. We identified nine cases that are carriers of pathogenic germline mutation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 50 publications
(62 reference statements)
3
31
0
Order By: Relevance
“…The high proportion of AJ individuals in our cohort (14.0%) contributed to the high overall prevalence observed. Multiple other founder variants were also detected in different populations in our study, including the c.3922G>T (p.Glu1308Ter) variant in BRCA2 that we found in almost half of the variant positive individuals with ancestry from PR, consistent with previous findings (32). We report, for the first time, prevalence estimates in a number of diverse populations, including African American and Hispanic/Latino populations for which these estimates did not previously exist.…”
Section: Discussionsupporting
confidence: 92%
“…The high proportion of AJ individuals in our cohort (14.0%) contributed to the high overall prevalence observed. Multiple other founder variants were also detected in different populations in our study, including the c.3922G>T (p.Glu1308Ter) variant in BRCA2 that we found in almost half of the variant positive individuals with ancestry from PR, consistent with previous findings (32). We report, for the first time, prevalence estimates in a number of diverse populations, including African American and Hispanic/Latino populations for which these estimates did not previously exist.…”
Section: Discussionsupporting
confidence: 92%
“…In our study of 664 breast cancer patients from Guatemala, 11% (73/664) were found to carry pathogenic mutations in high and medium penetrance breast cancer susceptibility genes. Guatemalan women have a higher ratio of deleterious BRCA1/BRCA2 mutations (2.8) than US Hispanic women or other Latin American populations [3][4][5][6]. The higher BRCA1 mutation rate is attributable to the high prevalence of the c.212 + 1G > A and c.799delT mutations.…”
Section: Discussionmentioning
confidence: 98%
“…Genetic testing for germline mutations in breast cancer susceptibility genes can identify individuals with a higher risk of developing breast cancer, but there is limited information on the mutation pro le of many Latin American populations [2,3] Hall et al documented that Latin American women referred for genetic testing have equal or higher rates of BRCA1 and BRCA2 mutations (15%) as other groups [4]. The frequency and spectrum of hereditary cancer gene mutations have been described in Latin American and US Hispanic populations [5][6][7][8]. However, cancer disparities among US Hispanic subgroups may be further masked because they tend to be aggregated as a monolithic group in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…In our study of 664 breast cancer patients from Guatemala, 11% (73/664) were found to carry pathogenic mutations in high and medium penetrance breast cancer susceptibility genes. Guatemalan women have a higher ratio of deleterious E1308X in Puerto Rico [3,5,7]. One recurrent mutation that has been documented in several populations across Latin America and US Hispanics is the Jewish founder mutation BRCA1 185delAG [4,28].…”
Section: Discussionmentioning
confidence: 99%
“…documented that Latin American women referred for genetic testing have equal or higher rates of BRCA1 and BRCA2 mutations (15%) as other groups [4]. The frequency and spectrum of hereditary cancer gene mutations have been described in Latin American and US Hispanic populations [5][6][7][8]. However, cancer disparities among US Hispanic subgroups may be further masked because they tend to be aggregated as a monolithic group in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%